The “Estia” scheme in Cyprus: A social policy mirage? - Andreou, Sofia N.; Koutsampelas, Christos (My University, 2019)
Emerging from the 2013 crisis, Cyprus is now faced with one of the highest rates of Non-Performing Loans in Europe. In an attempt to protect the first residence of distressed borrowers and contribute to financial stability, the government has proposed the Estia scheme, as a solution based on social policy criteria. But is it quite so?